2022
DOI: 10.1177/10105395221129113
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity and Its Associated Factors Among Malaysian Adults: Finding From the National Health and Morbidity Survey 2019

Abstract: In 2016, World Health Organization (WHO) estimated more than 650 million obese adults, resulting in a country’s health burden. This study aims to determine the prevalence of obesity and its associated factors among Malaysian adults. A total of 5820 respondents, aged 18 to 59 years, from the National Health and Morbidity Survey 2019, were included for the data analysis. The prevalence of obesity was described and multivariate analyses were conducted to determine the factors associated with obesity. The prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Risk factors such as abdominal obesity and obesity were also included in this analysis. [19][20][21][22]…”
Section: Other Variablesmentioning
confidence: 99%
“…Risk factors such as abdominal obesity and obesity were also included in this analysis. [19][20][21][22]…”
Section: Other Variablesmentioning
confidence: 99%
“…Furthermore, according to Oo et al (2019), the Asia Roundtable on Food Innovation for Improved Nutrition (2016) calculated that the rising rate of obesity will cost between RM4.26 billion and RM8.53 billion. According to Chong et al (2022), in Malaysia, a countrywide survey by National Health and Morbidity Survey (NHMS) found that the prevalence of obesity rose from 15.1% to 17.7% and then 19.9% in 2011-2015 and 2019-2020, respectively. In addition, 20.1% of Malaysian adults between 18 and 59 were obese (Chong et al, 2022).…”
Section: Prevalence Of Obesitymentioning
confidence: 99%
“…According to Chong et al (2022), in Malaysia, a countrywide survey by National Health and Morbidity Survey (NHMS) found that the prevalence of obesity rose from 15.1% to 17.7% and then 19.9% in 2011-2015 and 2019-2020, respectively. In addition, 20.1% of Malaysian adults between 18 and 59 were obese (Chong et al, 2022).…”
Section: Prevalence Of Obesitymentioning
confidence: 99%
“…The Indian community resided in estates owned by British colonial authorities or private companies, which have since transformed into suburban areas. As higher prevalence of obesity was observed among non-Chinese ethnic groups [25][26][27][28], this could potentially reflect in a higher prevalence of obesity at non-urban areas. However, national surveys in Malaysia found no evidence of differences in the prevalence of obesity between the general urban rural divide [29].…”
Section: Introductionmentioning
confidence: 99%